2020
DOI: 10.1007/s11427-019-1772-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2-induced proliferative endoplasmic reticulum stress participates in Kawasaki disease-related pulmonary arterial abnormalities

Abstract: Clinical cases have reported pulmonary arterial structural and functional abnormalities in patients with Kawasaki disease (KD); however, the underlying mechanisms are unclear. In this study, a KD rat model was established via the intraperitoneal injection of Lactobacillus casei cell wall extract (LCWE). The results showed that pulmonary arterial functional and structural abnormalities were observed in KD rats. Furthermore, proliferative endoplasmic reticulum stress (ER stress) was observed in the pulmonary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Our data, firstly, demonstrated that acute/subacute phase ratio of RV-PA coupling is an independent risk factor for CAL in KD children. Multisystemic vasculitis was the most characteristic pathological finding in KD children: in the coronary artery, medium-sized coronary dilatation, aneurysms and narrowing, and small coronary arterioles dilatation, endothelial cell injury, platelet aggregation with thrombosis, and stenotic lumen with thickened walls [23]; in the pulmonary artery, pulmonary artery dilation, inflammatory cell infiltration, vascular hyperpermeability, a large number of capillary networks formation, and neovascularization surrounding pulmonary nodules [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Our data, firstly, demonstrated that acute/subacute phase ratio of RV-PA coupling is an independent risk factor for CAL in KD children. Multisystemic vasculitis was the most characteristic pathological finding in KD children: in the coronary artery, medium-sized coronary dilatation, aneurysms and narrowing, and small coronary arterioles dilatation, endothelial cell injury, platelet aggregation with thrombosis, and stenotic lumen with thickened walls [23]; in the pulmonary artery, pulmonary artery dilation, inflammatory cell infiltration, vascular hyperpermeability, a large number of capillary networks formation, and neovascularization surrounding pulmonary nodules [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%